Implementasi Metode Six Sigma DMAIC Untuk Menurunkan Defect Produk Cereal Opak - Cipto Suparman; Rakay Edhiargo Toyosito; Lifia Citra Ramadhanti (UNISTEK, 2026)
This study at PT RRC aims to address the high volume of defective opaque cereal products using the Six Sigma (DMAIC) approach, combined with RCA and FMEA. Pareto analysis revealed that tough texture was the most dominant defect, contributing 70% of total defects. The initial process capability was 3.21 Sigma (DPMO 43,400). RCA and FMEA identified the root cause as manual water volume measurement based on the operator's visual estimation (RPN 448). As a solution, a semi-automatic digital flow meter system was installed. Consequently, the defect dropped to 2,575 kg/month, the RPN decreased to 128, and the process capability significantly improved to 4.28 Sigma (DPMO 2,720). This IDR 15,736,000 investment successfully saved the company IDR 329,460,000 per month